Rancang Bangun Aplikasi Pencatatan Keuangan dan Manajemen Pesanan untuk Bisnis Usaha Lontong - Rafiussani, Moh. Izza Akhyar; Armin, Aidil Primasetya (Jurnal Ilmu Siber dan Teknologi Digital, 2024)
Purpose: This study aims to design, develop, and evaluate an Android-based application for financial recording and order management tailored to a micro-enterprise (a lontong food stall) operated by Mr. Sutrisno, addressing the lack of structured transaction recording and disorganized order handling. Methodology/approach: Following a case-study approach in Indonesia, the application was built iteratively using Personal Extreme Programming (PXP) with Android Studio, Kotlin, and Room Database. Functional verification employed Black-Box Testing, while usability was assessed through Usability Testing (6 participants) and the UMUX-Lite questionnaire. Results/findings: Black-Box Testing yielded 100% pass rates across all core functions. Usability Testing showed that 100% of participants found the interface intuitive and input processes clear; all rated the financial recording and profit-loss reporting features as most beneficial, 50% regularly used the statistics module, and 83% reported no significant difficulties. UMUX-Lite produced an average score of 91.7, indicating very high perceived usability. Conclusions: The application successfully fulfills its objectives by combining reliable functionality with high user satisfaction, effectively streamlining financial and order processes for the target UMKM. Limitations: Findings are based on a single Android-only case study without iOS/web support, limited feature scope (basic income/expense recording and order organization), and a short evaluation period. Contribution: This research delivers a practical, user-centered solution for UMKM digitalization and provides a replicable development and evaluation framework for similar small business applications.